Accuracy of Mathematical Models and Process Simulators for Predicting the Performance of Gas-Separation Membranes - Yousef Alqaheem (Eng)
A membrane unit for gas separation is not available in most process simulators, and therefore it needs to be built manually. However, the developed units are based on assumptions, and the system is solved numerically. The accuracy of these models with industrial data is rarely discussed in the literature, but it is needed to confirm the reliability of process simulators. In this work, the membrane unit was developed in two different simulation software such as the commercial UniSIM® and the freeware CAPE-OPEN to CAPE-OPEN (COCO). In UniSIM®, the membrane module was built internally using a component splitter, spreadsheet, and adjust functions. In COCO, the membrane unit was developed by program coding with the external computational software, Scilab. The developed membrane units were assessed with field data for fuel gas conditioning. Results show that the membrane unit was easier to build in UniSIM® but when calculating the flowrate and composition of all compounds at the permeate and retentate sides, UniSIM® gives an error of 17.4% while COCO gives a slightly lower error of 17.1%. The high error was related to the effects of plasticization and concentration polarization, which were not taken into consideration in the mathematical model.